2013
DOI: 10.1016/j.scitotenv.2013.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Modeling particulate matter emissions during mineral loading process under weak wind simulation

Abstract: ► There are limitations in applying the empirical models to predict PM emission factors for mineral loading under weak winds. ► We modeled particulate matter emission factor of mineral loading processes under weak winds. ► A new approach of logistical function was developed and tested. ► New model focused on the effect of wind velocity. ► The new model works well for simulating stacker mineral loading processes. a b s t r a c t a r t i c l e i n f o The quantification of particulate matter emissions from miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…The high uncertainty of gas and other fossil fuel price reduces the security and stability of electricity supply and then impacts the economy [33]. Air pollutants emitted from fossil fuel, such as particular matters [34][35][36] and carbon emission [37], also cause environmental and climatic risks [38,39]. The well-known examples are the 1973-1974 Arab oil embargo and the 2000-2001 California electricity crisis.…”
Section: Impacts On Global Energy Security and Stabilitymentioning
confidence: 99%
“…The high uncertainty of gas and other fossil fuel price reduces the security and stability of electricity supply and then impacts the economy [33]. Air pollutants emitted from fossil fuel, such as particular matters [34][35][36] and carbon emission [37], also cause environmental and climatic risks [38,39]. The well-known examples are the 1973-1974 Arab oil embargo and the 2000-2001 California electricity crisis.…”
Section: Impacts On Global Energy Security and Stabilitymentioning
confidence: 99%
“…PM generated during mining operations at the workplace (called "bench") disperses in the mine by moving to several benches and contributes to the enhanced concentration at different parts of the mine . However, only a few studies have reported detail information about generation, estimation and contribution of PM during mining operations (Marrugo-Negrete et al 2014;Zhang et al 2013;Chakraborty et al Citation details: Patra, A., Gautam, S., Majumdar, S., . Prediction of particulate matter concentration profile in an opencast copper mine in India using an artificial neural network model.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited studies are available on physico-chemical composition of PM 10 that is responsible for adverse health effects. The sources of PM emission in opencast coal mines include blasting and drilling operations, transportation of coal and overburden on haul roads, coal handling plant operation, loading and transport of overburden and coal by shovel-dumper combination, crushing, conveying, and handling of overburden by draglines, and vehicular emission from unpaved roads (Zhang et al 2013). In addition to the above mentioned sources, coal mine fire has been found to be one of the major sources of PM emission (Pandey et al 2014).…”
Section: Introductionmentioning
confidence: 99%